Analisis Pengaruh Kualitas Informasi Laporan Keuangan Syariah terhadap Keputusan Investasi - Dewi Fajar Ayu; Dilla Puspita; Kiky Zulkifli (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the influence of the quality of information in Islamic financial statements on investment decisions, using a qualitative approach. Islamic financial statements not only present relevant and reliable financial information but also reflect adherence to Islamic principles such as justice, transparency, and social responsibility. The quality of information in financial reporting is believed to be a key factor in shaping investor perceptions, particularly for entities based on Sharia principles. The data in this study were obtained through a literature review of academic sources and Islamic accounting standards, as well as a document analysis of financial reports from several Sharia-compliant companies listed on the Indonesian capital market. The analysis was conducted descriptively and interpretively to evaluate the extent to which the characteristics of Islamic financial statements influence investment considerations. The findings indicate that high-quality information in financial reports—characterized by transparency in Sharia business activities, zakat disclosure, and compliance with PSAK Syariah—can enhance investor trust. This has a positive impact on the tendency of investors to invest in a more conscious and ethical manner. This study contributes to reinforcing the importance of transparency and accountability in Sharia-based financial reporting as a foundation for investment decision-making aligned with Islamic values.